Biochemical and biophysical studies on SilE from the sil silver resistance locus - Asiani, Karishma (2017)
Metal ions such as silver (Ag+), mercury (Hg2+), zinc (Zn2+) and copper (Cu+/Cu2+) have a long history of antimicrobial usage and some, such as Cu+/Cu2+, Ag+ and Zn2+ compounds are still used as antimicrobials. Prior to the introduction of antibiotics, Ag+ was arguably the most important antimicrobial and with the rapid emergence of antibiotic resistance, interest in Ag+ and its compounds as alternative antimicrobials have recently been revived. However, resistance to Ag+-based compounds has been emerging, with initial reports of carriage of silver resistance on a Salmonella enetrica serovar Typhimurium multi-resistance plasmid pMG101 isolated from burns patients in 1975. The proposed model for the mechanism of Ag+ resistance encoded by the sil genes from pMG101 involves export of Ag+ ions via an ATPase (SilP), an RND family effluxer (SilCFBA) and a periplasmic chaperone of Ag+ (SilE). SilE is a periplasmic protein predicted to be intrinsically disordered until it binds Ag+ ions. This hypothesis was tested using structural and biophysical studies which showed that SilE is an intrinsically disordered and unstructured protein in its free apo-form, but folds to a compact, defined structure upon optimal binding of six Ag+ ions in its holo-form. Sequence analyses and site-directed mutagenesis established the importance of histidine and methionine containing motifs for Ag+-binding, and identified a nucleation core that initiates Ag+-mediated folding of SilE. The data show that SilE is a molecular metal sponge absorbing up to a maximum of eight Ag+ ions.